PERANGKAT KERAS UNTUK PENGATUR JENDELA OTOMATIS TERHADAP PERUBAHAN SUHU PADA RUANGAN BERBASIS MIKROKONTROLER - , OBERLIN TUA PASARIBU, Muhammad Arrofiq, S.T.,M.T.,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Chili or capsicum annuum is a plant that is very basic to human needs at this time in which the plants require a suitable temperature in order to develop properly. Stabilizing the room temperature manually is less inefficient. Therefore to facilitate the controlling, each side of the room is placed window automatic adjust the temperature on the side of the room. Application of automatic window on green house will provide convenience for farmers to stabilize green house or knowing the desired temperature in the room. By simply pressing the desired temperature and then stabilize the room can be controlled automatically without the hassle of opening and closing the windows one by one. Temperature suitable for the cultivation of pepper plants is celsius. The window will close and open if: 1. Above room temperature celsius, then a window will open and the fan will spin, so the room temperature can be neutralized. 2. Room temperature under celsius, then the existing lights as a heating device that is inserted so that the room temperature can be achieved. 3. Room temperature celsius, the window does not move or in a closed state.